Applicability of the general data protection regulation in health clinics - Lopes, Isabel Maria (2018)
The GDPR aims to ensure the coherence of natural persons' protection within the European Union (EU), comprising very important innovative rules that will be applied across the EU and will directly affect every Member State. Furthermore, it aims to overcome the existing fragmented regulations and to modernise the principles of privacy in the EU. This regulation will come into force in May 2018, bringing along several challenges for citizens, companies and other private and public organisations. The protection of personal data is a fundamental right. The GDPR considers a 'special category of personal data', which includes data regarding health, since this is sensitive data and is therefore subject to special conditions regarding treatment and access by third parties. This premise provides the focus of this research work, where the applicability of the GDPR in health clinics in Portugal is analysed. The results are discussed in light of the data collected in the survey and possible future works are identified.